Silicon nanocrystals for nonlinear optics and secure communications. Issue 12 (15th October 2015) - Bisadi, Z.; Mancinelli, M.; Manna, S.; Tondini, S.; Bernard, M.; Samusenko, A.; Ghulinyan, M.; Fontana, G.; Bettotti, P.; Ramiro‐Manzano, F.; Pucker, G.; Pavesi, L.
Abstract : Silicon nanocrystals (Si‐nc) are reviewed here for their interesting optical applications. On the one hand, they do exhibit quantum confinement effects. This allows turning silicon into a light‐emitting material where luminescence can be excited by electrical injection. On the other hand, small sizes, large surfaces, and dielectric mismatch between the core and the surrounding matrix increase dramatically the nonlinear optical coefficients. This allows using Si‐nc as a nonlinear material in different waveguide configurations. In this paper, we discuss specifically two different applications of Si‐nc: (i) as a nonlinear material in various devices, e.g., in bistable optical cavities, in waveguide optical mode monitors that are based on two‐photon excited luminescence detection, and in wavelength shifters by using four‐wave mixing (FWM); (ii) as an entropy source for quantum random number generation, the key device for cryptography. (a) Top view optical image of a Si‐nc‐based whispering‐gallery mode (WGM) microdisk resonator, vertically coupled with a bus waveguide. (b) Detail of the coupling zone. (c) Normalized waveguide transmission spectrum over a wide spectral range. The inset shows a blow up of a resonance with the radial and azimuthal mode orders and the Q factor value indicated. Abstract : Silicon nanocrystals widen the scope of silicon photonics by providing an active material where light emission and optical nonlinearities are enhanced. In this Feature Article, the authors describe several applications of silicon nanocrystals in integrated optical devices towards their use for frequency conversion, optical mode imaging, light emission and quantum random number generation.